2018
DOI: 10.1002/jcla.22581
|View full text |Cite
|
Sign up to set email alerts
|

Distribution characteristics of different human papillomavirus genotypes in women in Wuhan, China

Abstract: BackgroundHuman papillomaviruses (HPVs) are strongly associated with the development of cervical carcinoma, and the distribution of HPV genotypes varies regionally.MethodsTo investigate the distribution characteristics of different genotypes of HPV infection in women in Wuhan, China, a total of 13 775 patients were enrolled over 2 years.ResultsOf these, 2436 patients were infected with HPVs, and the total infection rate was 17.68%. The infection rate of high‐risk HPV (HR‐HPV) was significantly higher (13.96%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 39 publications
(117 reference statements)
4
37
2
Order By: Relevance
“…In Fujian province, the main genotypes of HR HPV were HPV16, 52, 58, 53, and 33 . In Hubei province, the main genotypes of HR HPV were HPV 52, 16, 58, 39, and 51 . Interestingly, our results were also different from previous data from Meizhou city in northeastern Guangdong, which showed that the top five HR HPV genotypes were HPV16, 52, 58, 18, and 53 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In Fujian province, the main genotypes of HR HPV were HPV16, 52, 58, 53, and 33 . In Hubei province, the main genotypes of HR HPV were HPV 52, 16, 58, 39, and 51 . Interestingly, our results were also different from previous data from Meizhou city in northeastern Guangdong, which showed that the top five HR HPV genotypes were HPV16, 52, 58, 18, and 53 .…”
Section: Discussioncontrasting
confidence: 99%
“…The HPV infection rate varies markedly in China due to its large population and territory. Our results showed that the prevalent detection of any HPV subtypes among gynecological outpatients in Guangdong was 20.16%, which was higher than HPV prevalence in Hubei (17.68%) and lower than that in Fujian (38.3%) and Zhejiang (22.3%) . Considering the same laboratory method (Chaozhou Hybribio Limited Corporation, Chaozhou, China) in HPV detection among these studies, the diversity in HPV prevalence might mainly be attributed to geographical variation.…”
Section: Discussionmentioning
confidence: 57%
“…The HPV prevalence among women in Dali Bai Autonomous Prefecture (7.6%) was lower than previous studied reported the prevalence rate in the Shangri‐le, Lijiang, and other northwest regions of Yunnan (26.3%, 10.9%, and 18.0%, respectively) . In addition, the HPV prevalence was lower than that reported for most areas in China, such as Guizhou (15.1%), Jiangxi (22.49%), Shanghai (18.98%), Wuhan (17.68%), Tianjin (14.71%), and Guangzhou (12.32%) . Furthermore, the HPV prevalence in Dali area was also lower than the global prevalence of 11.7% .…”
Section: Discussionmentioning
confidence: 58%
“…The previous studies from different areas in China proved that the overall HPV infection rates were 22.4%, 38.3%, 17.6%, and 24.1%, respectively. However, our research suggested that the overall prevalence of HPV infection was 74.0% among the HSIL and ICC women.…”
Section: Discussionmentioning
confidence: 92%